THE IMPACT OF NURSING CARE ENVIRONMENT ON BEHAVIOURAL DISTURBANCES IN DEMENTIA: A LITERATURE REVIEW - Dwikarlina, Intan (Universitas Muhammadiyah Ponorogo, 2024)
Most of the dementia population will suffer from behavioural and psychological symptoms of dementia (BPSD), causing them to undergo progressive disturbances such as agitation, depression, elation, delusions, and hallucinations. Most evidence favours non-pharmacological intervention, including managing the physical environment settings, to tackle this issue. Adjusting the physical environment care will massively support people with dementia to continue their daily living. Providing a better nursing care environment has a significant impact on their orientation. Giving them a home-like and social opportunity allows them to regain their sense of normal life. Access to sensory stimulation will aid them to feel comfortable and promote better sleep. The green neighbourhood creates reciprocity feelings among people with dementia toward their environment. Tailoring the physical environment design can help lessen the behavioural symptoms of people with dementia, including their agitation, apathy, and depressive complaints. More high-quality trials and interventions with bigger sample sizes are required